On zeroes of the polynomials of elliptic Jacobi functions - Kholyavka, Ya.M. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
An estimate of the number of zeros of the function $F(r)=P(r,{\rm sn} r)$, where $P(X, Y)\in C [X, Y]$,  and ${\rm sn}  z$ is the Jacobian elliptic function, is obtained.